POTENSI DAN PROSPEK PENGEMBANGAN PRODUKSI JAGUNG (Zea mays L.) DI KOTA SAMARINDA (Potency and Prospect of Corn Production Development (Zea mays L.) in Samarinda City) - SEBASTIAN ALLESANDRO SALELUA; SYARIFAH MARYAM (Universitas Mulawarman (University of Mulawarman), 2018)
The development of corn production is an aspect in agricultural development. The research was done to know potency and prospect of corn production in Samarinda City. The research was conducted from October to December 2017. This research used time series data during 9 years from 2006 to 2014 by using simple linear regression to know potency and prospek of corn production in future. The result of research shows corn production in Samarinda City in 2006-2014 decreased. Corn production in Samarinda City is less developed, futhermore the corn farming should be managed by intensification program.